Social Values of Wetu Telu and Their Relevance to Formal Education in Bayan, North Lombok - Sukran Nizar Hilman; Saliman Saliman (Yayasan Keluarga Guru Mandiri, 2026)
Local wisdom is very important for maintaining cultural identity and social values in traditional communities, especially in the face of rapid social change and globalization. This paper will determine the social values inherent in the Wetu Telu local wisdom of the Bayan community in North Lombok, as well as considering how it can be applied to school education. In this study, a qualitative approach was used. In-depth interviews, participant observation, focus group discussion, and document analysis were used as methods of collecting data. Eight informants were chosen for the study: customary leaders, religious leaders, and community elders. The results indicate that Wetu Telu indigenous wisdom consists of eight fundamental social values: religiosity, cultural preservation, cooperation, kinship, politeness, responsibility, solidarity, and morality. These values are reflected in traditional practices, community events, and daily social engagements, and form a moral code that guides community living. Moreover, these values apply to formal education, especially in the emphasis on character education and cultural responsiveness in learning. This research contributes to the development of local wisdom research through the systematic classification of the social values inherent in Wetu Telu. Moreover, it provides a theoretical connection between regional prudence and institutional educational practices, thus contributing to culturally based education.